2010
DOI: 10.1542/peds.2009-1021
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pentavalent Rotavirus Vaccine in a Large Urban Population in the United States

Abstract: In this setting, a complete series of RV5 was highly effective against severe rotavirus AGE. Partial immunization also conferred substantial protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
112
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(129 citation statements)
references
References 22 publications
12
112
0
5
Order By: Relevance
“…Our VE estimates of RV5 are very similar to those found in other US evaluations. [13][14][15][16][17][18] We also found an overall high VE of a 2-dose mixed series.…”
Section: Discussionsupporting
confidence: 63%
“…Our VE estimates of RV5 are very similar to those found in other US evaluations. [13][14][15][16][17][18] We also found an overall high VE of a 2-dose mixed series.…”
Section: Discussionsupporting
confidence: 63%
“…During the study until the end of the 2003-2004 winter season the G1;P [8] genotype was widespread while G9:P [8] remained rare. A majority of severe rotavirus gastroenteritis requiring hospitalization may be prevented by the widespread use of rotavirus vaccines [52][53][54]. Noroviruses are the second leading causative agent of gastroenteritis in hospitalized young children and such infections are less severe than those caused by rotavirus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent effectiveness studies in the USA and Nicaragua showed that RV5 is effective in protecting against rotavirus-related hospitalisations , Boom et al 2010. However, because of the variation in the regional and global distributions of rotavirus serotypes, it is important to account for local surveillance data, if available, to accurately predict vaccine effectiveness in regions where no trials or effectiveness studies have been conducted (Gentsch et al 1996).…”
mentioning
confidence: 99%